Reliability Perception for Islamic Websites - Nassr, rasheed Mohammad; mahmud, murni (Journal of Computing Technologies and Creative Content, 2019)
Muslims use the internet as a medium to disseminateIslam. This is seen as necessary due to the wide distribution of Muslimsglobally and difficulties to establish Islamic centres to teach Muslimsand perform dawah (delivering message). Along with this, whetherIslamic online information can be trusted has been questioned. Theincrease in cases of finding unreliable and sometime Islamophobiacontent websites and questionable authenticity of online informationhas led researchers and organisations to respond to the reliabilityissues. This study explores the reliability perception in relation toIslamic websites from Muslim users’ perspective. The findings suggestthat availability of Quranic verses, availability of citations forauthentic prophetic biography, referencing authentic Hadith, reflectingmathahib perspectives, scholars’ and organisations’ involvement, andrecommended websites’ content features are the major factors thatinfluence the reliability of Islamic websites. Those factors cultivate thebelief that Islamic websites have reliable, authentic, and wellreferenced content. Emphasising these factors would increase theperceived level of reliability of Islamic websites, which would increasethe acceptance for the Islamic messages delivered.